Tip-vortex investigation on a rotating and pitching rotor blade - Goerttler, A.; Braukmann, J.N.; Schwermer, T.; Gardner, A.D.; Raffel, M. (My University, 2017)
The blade-tip vortex of a rotating and pitching DSA-9A blade was investigated numerically and experimentally. Numerical computations were performed using DLR’s finite volume solver TAU and experimental data was gathered by using particle image velocimetry (PIV) carried out in a stereoscopic setup at the rotor test facility in G¨ottingen (RTG). Algorithms deriving the vortex position, swirl velocity, circulation and core radius were implemented. The agreement is better the lower the wake age, with numerical dissipation enlarging the blade-tip vortex in an artificial manner with increasing wake age. Nevertheless, the numerical simulations are able to predict swirl velocity and circulation well and help understanding the growth and development of the blade-tip vortices. A comparison with a nonrotating version of this blade showed that the circulation of the nonrotating blade was in the same order.